Local Drivers of Change in Southern Ocean Ecosystems: Human Activities and Policy Implications - Grant, Susie M.; Waller, Cath L.; Morley, Simon A.; Barnes, David K. A.; Brasier, Madeleine J.; Double, Mike C.; Griffiths, Huw J.; Hughes, Kevin A.; Jackson, Jennifer A.; Waluda, Claire M.; Constable, Andrew J. (Frontiers in Ecology and Evolution, 2021)
Local drivers are human activities or processes that occur in specific locations, and cause physical or ecological change at the local or regional scale. Here, we consider marine and land-derived pollution, non-indigenous species, tourism and other human visits, exploitation of marine resources, recovery of marine mammals, and coastal change as a result of ice loss, in terms of their historic and current extent, and their interactions with the Southern Ocean environment. We summarise projected increases or decreases in the influence of local drivers, and projected changes to their geographic range, concluding that the influence of non-indigenous species, fishing, and the recovery of marine mammals are predicted to increase in the future across the Southern Ocean. Local drivers can be managed regionally, and we identify existing governance frameworks as part of the Antarctic Treaty System and other instruments which may be employed to mitigate or limit their impacts on Southern Ocean ecosystems.